1984
DOI: 10.1677/joe.0.1000219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypothalamic neuropeptides on corticotrophin release from quarters of rat anterior pituitary gland in vitro

Abstract: The effect of six hypothalamic peptides on the basal release of ACTH and that induced by arginine vasopressin (AVP) or by ovine corticotrophin releasing factor (oCRF) from fragments of the rat anterior pituitary gland incubated in vitro was investigated. Dose–response curves to AVP and to oCRF were obtained, and the response to a low dose of oCRF was potentiated by a low dose of AVP. Basal release of ACTH was not affected by any of the peptides in concentrations in the range 10−12 to 10−6 mol/l, and only subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…In vitro incubation of anterior pituitaries and RIA of ACTH Anterior pituitary incubations were performed essentially by the method described previously (Nicholson et al, 1984). Briefly fresh anterior pituitaries from SD and PVG rats were quartered and two quarters incubated per well in 1 ml KrebsRinger medium containing bovine serum albumin (BSA, 0.1%) and ascorbic acid (0.01%) under 95% 02/5% CO2 at 37°C.…”
Section: Animal Proceduresmentioning
confidence: 99%
“…In vitro incubation of anterior pituitaries and RIA of ACTH Anterior pituitary incubations were performed essentially by the method described previously (Nicholson et al, 1984). Briefly fresh anterior pituitaries from SD and PVG rats were quartered and two quarters incubated per well in 1 ml KrebsRinger medium containing bovine serum albumin (BSA, 0.1%) and ascorbic acid (0.01%) under 95% 02/5% CO2 at 37°C.…”
Section: Animal Proceduresmentioning
confidence: 99%
“…In vitro studies suggested that normal corticotroph only responds to somatostatin with inhibition of ACTH release if the cells have been cultured in glucocorticoid free medium (70)(71)(72)(73)(74). In agreement with this is the finding that ACTH secretion in normal individuals is not affected by infusion of somatostatin or octreotide but is affected in patients with Addison's disease (75,76).…”
Section: Somatostatin Analoguesmentioning
confidence: 70%
“…However, the influence of SP on the release of other anterior pituitary hormones is more complex. It has been reported that corticotropinreleasing hormone and arginine-vasopressin-stimulated release of corticotropin from anterior pituitaries was inhibited by addition of SP to the incubation medium (Nicholson et al, 1984). Recently, another study could not confirm any effect of SP on corticotropinreleasing hormone-stimulated release of corticotropin from dispersed anterior pituitary cell cultures (Chawdrey et al, 1990).…”
Section: Discussionmentioning
confidence: 99%